PERUBAHAN SIFAT KIMIA TANDAN KOSONG KELAPA SAWIT YANG DIFERMENTASI DENGAN EM4 PADA DOSIS DAN LAMA PEMERAMAN YANG BERBEDA - ABDUL RAHMAN TOIBY; ELFI RAHMADANI; Oksana Oksana (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2015)
This study was conducted from March to September 2013 at the Islamic State University of Syarif Kasim Sultan Riau and analysis of the chemical properties of compost made in BPTP Riau. This study aims to determine the dose and the duration of fermentation EM4 right to obtain compost oil palm empty fruit bunches with the best chemical properties. Oil palm empty fruit bunches are used are taken from PTPN V Lubuk Dalam and mixed with manure from cattle feces with ratio of 4:1. The method used was descriptive quantitative method consisting of 12 combinations of treatment and 1 control. The parameters measured were the content of N, P, K, C-Organic and pH. The results of this study indicated that EM4 and long curing compost may improve the chemical properties of oil palm empty fruit bunches, which the administration of 20 mL / L EM4 and curing 10 weeks old that A3B4 sample produces the best chemical properties. The content of N, P, K, and pH of the sample A3B4 respectively: 6,79%, 3,04%, 8,08%, and 9,93 %.